2013
DOI: 10.17221/599/2012-pse
|View full text |Cite
|
Sign up to set email alerts
|

Impact of site-specific weed management on herbicide savings and winter wheat yield

Abstract: There is much documentation in the scientific literature (e.g. Clay et al. 1999, Hamouz et al. 2006, Gerhards et al. 2012) that weeds are distributed in a patchy manner throughout agricultural fields. An aggregated distribution pattern of weed populations provides opportunity to reduce the herbicide application if site-specific weed management is adopted. Gerhards et al. (2002) achieved herbicide savings of 60% and 92% for dicotyledonous and monocotyledonous weeds, respectively, in spring barley (Hordeum vulga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Usually, the herbicide application window depends on weather conditions, weed species and crops, and can be as short as a two-to three-day window. Although some researchers have achieved interesting results in terms of weed detection and herbicide savings based on on-the-go weed detection systems and field surveys [56][57][58], they are time consuming and costly. It could delay the The optimization of weed management practices relies on timing weed control [51], as weed presence in the early crop season is a key component of the weed-crop competition and further yield loss [52,53].…”
Section: Prescription Mapsmentioning
confidence: 99%
“…Usually, the herbicide application window depends on weather conditions, weed species and crops, and can be as short as a two-to three-day window. Although some researchers have achieved interesting results in terms of weed detection and herbicide savings based on on-the-go weed detection systems and field surveys [56][57][58], they are time consuming and costly. It could delay the The optimization of weed management practices relies on timing weed control [51], as weed presence in the early crop season is a key component of the weed-crop competition and further yield loss [52,53].…”
Section: Prescription Mapsmentioning
confidence: 99%
“…A previous paper by Hamouz et al (2013) demonstrated that when using SSWM in winter wheat herbicide savings of 51-91% were possible for grass weeds and of 16-84% for dicotyledonous weeds in the same field. In winter rape, SSWM provided even greater post-emergent herbicide savings, ranging between 71.9% and 100%, depending on treatment (Table 4).…”
Section: Methodsmentioning
confidence: 99%
“…The threshold values used in winter rape are listed in Table 1. The threshold values and herbicides used in winter wheat are presented in Hamouz et al (2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Rizzardi and Fleck (2004), densities of 4 or more plants per m -2 of the common weed Bidens pilosa L. can limit the development of soybeans. Hamouz et al (2013) organized the management of weeds for a specific site on a 4 x 1.5-meter grid using a threshold of weed density of 0.02 to 0.20% (0.10 to 15.51 plants m -2 ). They found this procedure led to a reduction in herbicides needed from 15.6 to 100%, depending on the type of herbicide and threshold of application used.…”
Section: Weed Infestation Level Based On Expert Evaluationmentioning
confidence: 99%